(untitled) - Allen, G. C. (London, 1928)
The author, who was for several years a lecturer in a Japanese Government College, has tried to interpret the civilization and national character of Japan in the light of his experience and of his studies in that country. He describes the novel problems and phenomena which have been created by the attempt of the Japanese to graft the political, economic and educational institutions of the West on to their Oriental social organization. He deals with the influence of the West on the different phases of the national life, and with the attitude of the Japanese to Europe and America. Particular attention is given to industrial and financial development and to contemporary economic problems. There are chapters on the political system, on the social organization, and on the educational system; and there is a special study of the population problem.
Keywords: Japan,Nhật Bản,Nhật Bản,Nhật Bản,Japan; Economic conditions,Nền văn minh,Nền văn minh,Điều kiện kinh tế,Civilization